Evaluation of corrosion characteristics of mild steel in the acidic environment using Cocoyam and Almond leaves extracts as inhibitors - Christopher N Mbah; Deborah C Onyeabor; Bonaventure C Ugwuanyi; Michael G Anuta; Chukwunonso S Nebechi; Obinna L Iyida; Kingsley C Nnakwo (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2023)
The inhibition characteristics of Almond and Cocoyam leaves extracts on mild steel immersed in 1 M H2SO4 at immersion times of 24 h to 144 h have been investigated experimentally. The effects of various concentrations of the extracts on the corrosion rate and inhibition efficiency were also explored. The average corrosion rates (in mm yr-1) and inhibition efficiencies (in %) were determined at each extract concentration and immersion time. Results show that both extracts demonstrated excellent inhibition characteristics for mild steel in H2SO4 media as the corrosion rate of the mild steel decreased from 43.0096 mm yr-1 to 4.7019 mm yr-1 and 4.9528 mm yr-1 after adding 8 g/L of Cocoyam and Almond leaves extracts respectively. This can be linked with the adsorption of molecules of oxidative phytochemical constituents of the extracts on the mild steel surfaces which shielded the mild steel surfaces from further attack by the acid. Within the time range of the study, the inhibition efficiency of both Cocoyam and Almond leaves extracts increased with an increase in inhibitor concentration with maximum inhibition efficiencies of 70.15% and 56.67% recorded by Almond and Cocoyam leaves extracts respectively at concentrations of 8 g/L. Conclusively, Almond leaves extracts are better mild steel corrosion inhibitors than cocoyam leaves extracts, due to the lower pH value of Cocoyam leaf extract.